1991
DOI: 10.1139/b91-342
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy of barley root infection by the fungal pathogen Bipolaris sorokiniana

Abstract: An electron microscopic investigation of barley roots infected in vitro by Bipolaris sorokiniana showed the existence of an extracellular sheath on germ tubes and appressoria attached to the root surface. Growth of the fungus in the epidermis and outer cortex was predominantly intracellular, whereas in the inner cortex the hyphae observed were mainly intercellular. Hyphae could not be detected in the stele 24 or 72 h after inoculation. Enzymatic activity in the apex of penetration hyphae is a possible explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…The small diameter of the hyphae and the absence of dolipore septa indicate that a basidiomycete is probably not responsible for the formation of CWAs. CWAs, similar to the ones studied here, have more frequently been described in association with plant-pathogenic Ascomycota such as Bipolaris (Carlson et al, 1991), Botrytis (Archer and Cole, 1986), Colletotrichum (Mims and Vaillancourt, 2002;Wharton et al, 2001), Erisyphe (Smith, 1900), Fusarium (Beswetherick and Bishop, 1993;Griffiths and Lim, 1964;Smith and Peterson, 1985), Leptosphaeria (Roussel et al, 1999), Gaeumannomyces (Yu et al, 2010), Ophiobolus (Fellows, 1928), Trichoderma (Yedidia et al, 1999), and Verticillium (Griffiths and Lim, 1964;Griffiths, 1970;Storey and Evans, 1987). In most cases, they penetrate plants by use of penetration pegs which are thin tip-growing cellular protuberances, generally less than 1 m in diameter (Howard, 1997).…”
Section: Discussionsupporting
confidence: 78%
“…The small diameter of the hyphae and the absence of dolipore septa indicate that a basidiomycete is probably not responsible for the formation of CWAs. CWAs, similar to the ones studied here, have more frequently been described in association with plant-pathogenic Ascomycota such as Bipolaris (Carlson et al, 1991), Botrytis (Archer and Cole, 1986), Colletotrichum (Mims and Vaillancourt, 2002;Wharton et al, 2001), Erisyphe (Smith, 1900), Fusarium (Beswetherick and Bishop, 1993;Griffiths and Lim, 1964;Smith and Peterson, 1985), Leptosphaeria (Roussel et al, 1999), Gaeumannomyces (Yu et al, 2010), Ophiobolus (Fellows, 1928), Trichoderma (Yedidia et al, 1999), and Verticillium (Griffiths and Lim, 1964;Griffiths, 1970;Storey and Evans, 1987). In most cases, they penetrate plants by use of penetration pegs which are thin tip-growing cellular protuberances, generally less than 1 m in diameter (Howard, 1997).…”
Section: Discussionsupporting
confidence: 78%
“…deposition of electron-dense material between the cell wall and the plasma membrane has been observed ( Fig. 1; Carlson et at., 1991b), supporting the view that enzymes producing electron-dense material, which may seal leaky membranes, are active despite being locally exposed to toxin.…”
Section: Discussionmentioning
confidence: 96%
“…depending on the host tissue invaded. An electron microscopical investigation of barley roots infected by B. sorokiniana has shown that the fungal hyphae grow predominantly intercellularly in the cortex (Carlson et al, 1991b). Separation of the plasmalemma from the cell wall together with degeneration of host nuclei and organelles were changes commonly induced by infection, even in cells ahead of invading hyphae.…”
Section: Introductionmentioning
confidence: 99%
“…Root pathogens such as Bipolaris sorokiniana can reach the endodermis of Triticum aestivum (wheat) or barley roots within 2-3 d (Carlson et al 1991). The wilt-inducing pathogenic F. oxysporum massively invades all tissues of Pisum sativum (pea) roots until it reaches the xylem.…”
Section: Discussionmentioning
confidence: 99%